2014
DOI: 10.1111/joa.12220
|View full text |Cite
|
Sign up to set email alerts
|

Limb bone morphology, bone strength, and cursoriality in lagomorphs

Abstract: The primary aim of this study is to broadly evaluate the relationship between cursoriality (i.e. anatomical and physiological specialization for running) and limb bone morphology in lagomorphs. Relative to most previous studies of cursoriality, our focus on a size-restricted, taxonomically narrow group of mammals permits us to evaluate the degree to which 'cursorial specialization' affects locomotor anatomy independently of broader allometric and phylogenetic trends that might obscure such a relationship. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 85 publications
1
50
0
Order By: Relevance
“…A new finding in this study, however, is that asymmetry in external articular dimensions increases distally; and both the FA and DA show this pattern. Safety factors of bone (a ratio of fracture stress to peak functional stress, that is, how "over engineered" a bone is (Biewener, 1983)) have been documented to decrease distally along limbs (Alexander, 1981;Young et al, 2014), and patterns of bone functional adaptation likewise differ between the proximal and distal cortices of limb bones (Lieberman et al, 2003). Whether these biomechanical aspects of limb bones correspond with the proximodistal pattern in asymmetry cannot be made, however the link among them is compelling; it is possible that the distal portions of bone are more sensitive to their mechanical environment than proximal portions, and therefore lead to more asymmetry (Lieberman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A new finding in this study, however, is that asymmetry in external articular dimensions increases distally; and both the FA and DA show this pattern. Safety factors of bone (a ratio of fracture stress to peak functional stress, that is, how "over engineered" a bone is (Biewener, 1983)) have been documented to decrease distally along limbs (Alexander, 1981;Young et al, 2014), and patterns of bone functional adaptation likewise differ between the proximal and distal cortices of limb bones (Lieberman et al, 2003). Whether these biomechanical aspects of limb bones correspond with the proximodistal pattern in asymmetry cannot be made, however the link among them is compelling; it is possible that the distal portions of bone are more sensitive to their mechanical environment than proximal portions, and therefore lead to more asymmetry (Lieberman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…; Ruff, , ; Young et al. , ). Then, one‐way anova s were used to determine whether intensive selection for increases in bone length caused changes in the mean cross‐sectional properties (CSA, Z p ) and scaled bending strength (IR) of the Longshanks and Control tibiae.…”
Section: Methodsmentioning
confidence: 99%
“…improved running economy) and reduced bone safety factors (Young et al. ). Intra‐specifically, a study by Kemp et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors proposed the giraffe metapodials to be the seat of limb propulsion and elongation (Thompson, ; Colbert, ; McMahon, ). In proficient runners, it has been shown that the elongated distal elements are more energy efficient and increase stride length (Carrier, ; Christiansen, ; Lammers and German, ; Young et al, ). Our data show, however, that the metapodials of giraffes do not elongate more than other limb bones over their lifetime.…”
Section: Discussionmentioning
confidence: 99%